Studi Eksperimen Gasifikasi Pada Reaktor Fluidized Bed Dengan Bahan Bakar Ampas Tebu - Rudiyanto, Feri; , Nur Aklis, ST, M. Eng (2017)
Abstract The aims of the research is to determine the effect of fuel particle size on the performance of fluidized bed reactor. The research was permormed on reactor with a diameter of 454.38 mm and 908.5 mm combustion chamber high. The study used bagasse fuel with the variation of size 1.54 mm, 1.08mm, 0.708 mm and particles bed is silica sand used with the size of 0.54 mm. The combustion process for a once use 10 kg silica sand, chalk 1 kg, and bagasse 5 kg. The data are taken contained of the minimum speed of fluidization, reactor temperature, time of reaction, the length of time to boil the water by as much as 2 liters. The examination showed that the size of the fuel affects the speed of minimum fluidization. The average reactor temperature high of 207 (ºc). Fastest time to boil water as much as 2 liters is 33 minutes. on an examination by using bagasse size 1.54 mm. Greatest amount of heat is generated that is 2051.765 kJ conducted on the examination using bagasse fuel size 0.708 mm. Fastest time of reaction is 45 minute conducted on the examination by using a variation bagasse size of 1.54 mm